Vertical Gradient Temperature Difference of the Main Arch with Single Pipe Section in Tibet Based on Statistical Analysis - Tuo Shi; Nianchun Deng; Zheng Chen; Haoxu Li (Advances in Materials Science and Engineering)
A 75 m long experimental arch with a 1.6 m diameter was constructed in Tibet for a one-year test to determine the most unfavourable vertical temperature difference for a single pipe in the main arch of a concrete-filled steel tube arch bridge. Actual temperature observation data were used to analyse the vertical temperature difference in the single circular pipe arch rib using statistical methods. The standard value for the vertical temperature difference in the single pipe under a return period of 50 years was calculated. The results showed that the influence range of the vertical gradient temperature was 25 cm. The vertical temperature difference followed a lognormal distribution, and the standard values of the positive temperature difference at the upper and lower ends of the single pipe were 16 and 10°C, respectively; the standard values of the negative temperature difference at the upper and lower ends of the single pipe were both -8°C under a return period of 50 years. These results are considerably different from the values specified in the current Chinese code. These could serve as references for calculations involving arch bridges in Tibet with single circular pipes in the main arches.